Harga Jual dan Volume Penjualan Terhadap Pendapatan Toko Jaya dI Pusat Grosir PGS Surabaya - Nuryadi (Lembaga Pengembangan Kinerja Dosen, 2022)
This study aims to explain the effect of selling price and sales volume on the sales of Toko Jaya Aik, either partially or simultaneously. This type of research is quantitative research with a causal approach. The Toko Jaya Accounting Report 2018-2019 with a 2-month sample was used as a research taxi. Data was collected by means of internet literature research and literature research observations. Multiple linear regression analysis, F test, and T test were used for data analysis in this study. The results showed that the selling price had a positive and significant effect partially or simultaneously on Toko Jaya's bottom line. Sales have a positive and significant impact on Toko Jaya's bottom line, either partially or all at once